Sleep quality in elderly people with chronic pain: an integrative literature review (Research, Society and Development, 2023)
The aging process implies the emergence of numerous risk factors for changes in sleep such as chronic pain. Thus, the aim of this study was to review the literature on chronic pain and sleep quality in relation to the elderly, reporting the associations between these two variables. The research materials were obtained from the MEDLINE, LILACS and SCIELO databases, using the keywords chronic pain, elderly and sleep. Electronic searches resulted in 111 studies, 73 in the MEDLINE database, 36 in the SCIELO database and 02 in the LILACS database. A total of 04 studies met the eligibility criteria and were included in this review. The data obtained suggest that chronic pain is common among the elderly and is associated with depression, as well as poor quality of life and poor quality of sleep. It was possible to verify that the results of this analysis corroborate the literature, which is still scarce in terms of studies with this population, showing the need for further research in this area.